ICT Integration in Secondary Schools: Evaluating Ease of Use and Perceived Benefits for Effective Teaching and Learning (Journal of Asian Development Studies, 2024)
This research investigates the integration of Information and Communication Technology (ICT) in secondary schools, focusing on educators' perceptions of its ease of use and perceived benefits for effective teaching and learning. Utilizing a quantitative approach with a survey methodology, data was collected from 60 secondary schools across Lahore and Gujranwala districts, involving 310 secondary school educators (144 males and 166 females). A proportionate stratified sampling technique was employed, and a modified version of the QICT (Questionnaire on the Integration of ICT) was used to assess teachers' views on ICT integration. Five experts validated the instrument with a reliability coefficient of 0.789. Results indicate that ICT integration is crucial for enhancing teaching and learning in secondary schools. Teachers with ICT-related qualifications demonstrated a more significant influence on classroom ICT usage. The study found that teachers generally perceived ICT integration as easy and beneficial, noting improved teaching effectiveness and student engagement. Educators with advanced ICT skills were more effective in incorporating technology into their teaching practices. Overall, the research underscores the importance of ICT in creating dynamic and effective learning environments in secondary education.